Intensifying Australian Heatwave Trends and Their Sensitivity to Observational Data. Issue 4 (23rd April 2021) - Jyoteeshkumar reddy, P.; Perkins‐Kirkpatrick, Sarah E.; Sharples, Jason J.
Abstract: Heatwaves are an accustomed extreme event of the Australian climate, which can cause catastrophic impacts on human health, agriculture, and urban and natural systems. We have analyzed the trends in Australia‐wide heatwave metrics (frequency, duration, intensity, number, cumulative magnitude, timing, and season duration) across 69 extended summer seasons (i.e., from November‐1951 to March‐2020). Our findings not only emphasize that heatwaves are becoming hotter, longer, and more frequent, but also signify that they are occurring with excess heat, commencing much earlier, and expanding their season over many parts of Australia in recent decades. The Australian heatwave trends have strengthened since last observed Australian study was conducted. We also investigated the heatwave and severe heatwave trends at a local city‐scale using three different observational products (AWAP and SILO gridded datasets and ACORN_SATV2 station data) over selected time periods (1911–2019, 1911–1964, and 1965–2019). Results suggest that heatwave trends are noticeably different amongst the three datasets. However, the results highlight that the severe heatwave cumulative magnitude and their season duration have been increasing significantly in recent decades over Australia's southern coastal cities (like Melbourne and Adelaide). The climatological mean of the most heatwave and severe heatwave metrics is substantially higher in recent decades compared to earlier periods across all the cities considered. The findings of our study have significant implications for the development of advanced heatwave planning and adaptation strategies. Key Points: Australian heatwaves are becoming hotter, longer, frequent, occurring with excess heat, starting earlier, and extending their season duration Australian heatwave trends are noticeably different amongst gridded and in‐situ station datasets Heatwaves and severe heatwaves have increased rapidly in the recent decade compared to previous periods in the considered Australian cities